MODEL-MODEL PENGEMBANGAN KURIKULUM DAN SILABUS PEMBELAJARAN BAHASA ARAB - Zubaidi, Ahmad (IAIN Ponorogo, 2015)
Abstract: Syllabus refers to a lesson plan on a particular or group of subjects/ themes that covers standard of competency, basic competencies, learning materials, learning activities, indicators of competence achievement, assessment, allocation of time, and learning resources. The principles in developing syllabus are scientific, relevant,systematic, consistency, adequate, actual and contextual, flexible, and comprehensive. The procedures of syllabus development are reviewing and determining standard of competency, assessing and determining basic competencies, determining indicators of competence achievement, identifying learning materials, determining the type of assessment, determining the allocation of time, and determining the source of learning. There are various models of syllabus on learning Arabic as a foreign language. Each model has a concept in teaching Arabic with its own framework and aspect of skills.Â ØØ©Ø¡Ø§ÙÙÙØ§ Ø±Ø§ÙØ¹Ù ÙÙØ¹ ÙÙ ØªØ´Ù ÙØ°ÙØ§ Ø©ÙÙØ¹ÙÙ Ø§ Ø³ÙØ±Ø¯ÙØ§ ÙÙ Ø¹Ø¬Ù ÙØ£ Ø§Ù Ø©Ø¯Ø§Ù ÙÙ ÙØ¹ÙØ±Ø´Ù Ù Ø³ÙØ±Ø¯ØªÙØ§ Ø¬Ù Ø§ÙØ±Ø¨ ÙÙ Ø±Ø±ÙÙÙ Ø§Â ÙÙ Ø²ÙØ§Ù ØÙ ÙÙÙØªÙØ§Ù ØØªØ§ÙØ§ÙÙÙØ§ ÙØ°Ù ÙÙØ¥ ÙÙØµÙÙØ§ ØªØ§Ø±Ø´Ø¤Ù Ù ØØ³ÙØ±Ø¯ØªÙØ§ Ø©Ø·Ø´ÙØ£Ù ØØ³ÙØ±Ø¯ØªÙØ§ Ø¯Ø§ÙÙ Ù ØØ©ÙØ³Ø§Ø³ÙØ£Ø§ Ø©Ø¡Ø§ÙÙÙØ§ÙÂ Ø©Ø±ØµØ§Ø¹ÙÙ Ø§ ØØ©ÙØ¦ÙÙÙØ§Ù ØØ©ÙÙ Ø¸ÙÙÙ Ø§Ù ØØ©ÙØ¨Ø³Ø§ÙØªÙØ§Ù ØØ©ÙÙ ÙØ¹ÙØ§ :ÙÙÙØ±Ø±ÙÙÙ Ø§ Ù ÙÙ ØµØª ÙÙ Ø³Ø³Ø£ Ø©Ø«Ù Ù .Ø©Ø³Ø§Ø±Ø¯ÙØ§ Ø±Ø¯Ø§ØµÙ Ù ØØØ§ØªÙÙ Ø§Â ØØ©Ø¡Ø§ÙÙÙØ§ Ø±Ø§ÙØ¹Ù ÙÙÙØ¹ØªÙ Ø©Ø³Ø§Ø±Ø¯ :ÙÙ ÙØ³Ø§Ø±Ø¯ÙØ§ Ø±Ø±ÙÙÙ Ø§ Ù ÙÙ ØµØª ØªØ§ÙØ·Ø® Ø§Ù Ø£ .Ø©ÙÙÙÙ Ø´ÙØ§Ù ØØ©ÙÙÙØ±ÙÙ Ø§Ù ØØ©ÙÙØ§ÙØ³ÙØ§ÙÂ ÙÙÙØ¹Øª ØØ©ÙØ³Ø§Ø±Ø¯ÙØ§ Ø¯Ø§ÙÙÙ Ø§ Ø´ÙØªÙØª ØØªØ§ÙØ§ÙÙÙØ§ ÙØ°Ù ÙÙØ¥ ÙÙØµÙÙÙ ØªØ§Ø±Ø´Ø¤ÙÙ Ø§ ÙÙÙØ¹Øª ØØ©ÙØ³Ø§Ø³ÙØ£Ø§ Ø©Ø¡Ø§ÙÙÙØ§ ÙÙÙØ¹ØªÙ Ø©Ø³Ø§Ø±Ø¯Â Ø©ÙØ¨Ø±Ø¹ÙØ§ Ø©ØºÙÙØ§ Ù ÙÙØ¹ØªÙ ÙØ³Ø§Ø±Ø¯ÙØ§ Ø±Ø±ÙÙÙ Ø§ ÙÙ Ø¹Ø§ÙÙØ£ ÙØ§ÙÙ .Ø©Ø³Ø§Ø±Ø¯ÙØ§ Ø±Ø¯Ø§ØµÙ ÙÙÙØ¹Øª Ù Ø« ÙÙ Ø²ÙØ§ Ø¯ÙØ¯ØªØ ØÙ ÙÙÙØªÙØ§ Ø¨ÙÙØ³Ø£Â ÙÙ ÙØ£ Ø¨ÙØ§Ø¨Ø¬ )Ø©ÙÙØºÙÙØ§ ØªØ§Ø±Ø§ÙÙÙ Ø§Ù ( Ø©ÙØ¨Ø±Ø¹ÙØ§ Ø©ØºÙÙØ§ Ù ÙÙØ¹Øª ÙÙØ¨Ø·Øª ÙÙ Ù ÙÙØ§ÙÙ Ø¹ÙÙÙØ§ Ø§Ø°Ù ÙÙ ÙÙÙÙ .Ø©ÙØ¨ÙØ¬Ø£ Ø©ØºÙÙ.ÙÙÙØ¥ Ø¯ÙØªØ³Ù Ø³Ø³Ø£ ÙÙØ°Ù